The electronic books and their incidence in the reduction of the tax evasion in companies of the Huánuco province 2017 - Huaynate-Delgado, Elías T. (2019)
The objective of this study was to determine the extent to which electronic books affect the reduction of tax evasion in the companies of the Province of Huánuco. The study method was basic, the level of research by its nature meets the characteristics to be an applied research of descriptive - evaluative, non - experimental level whose methodological design is correlational transactional. The result shows that the 6720 data obtained at 57.10% (3837) affirm that they agree that there is a significant relationship between e-books and the reduction of tax evasion in the companies of the Province of Huánuco, while 22.81% (1533) of the respondents manifest their disagreement and 20.09% (1350) do not know do not think about it. It is concluded that, electronic books through their dimensions: electronic books and information, affect the reduction of tax evasion through its dimensions: income tax, general sales tax, tax administration, in the companies of Huánuco, as has been demonstrated at the time of testing the general hypothesis by the chi-squared test.